Parámetros productivos de reproductoras pesadas línea cobb 500 a la suplementación con calcio orgánico - Mendieta Gomez, Elizabeth Margarita (2015)
This research was conducted at the company incubator Rodriguez SAC, located in the city and province of Paiján, La Libertad department; in order to determine the effect of the addition of a kg of organic calcium on performance and egg quality of 500 Cobb 384 broiler breeder birds were employed under a complete block design at random, distributed in two treatments: T0 normal diet, T1 diet with addition of a kilo of Biocalcio and block age of the hen. For the parameter production rate, T1 was 45.1%, T0: 39.9%. Highly significant differences (p<0,01) were found. The age of the hen affected this feature (p<0,01). In the parameter number of eggs laid per hen per week, T1 was 3.2, T0: 2.8. Highly significant differences (p<0,01) were calculated. In parameter egg weight, T1 was 66.5g, T0: 65.7g. Highly significant differences (p<0,01) were calculated. Reproductive age increased this feature. In the characteristic egg mass, T1 was 210.1, T0: 184.2. Highly significant differences (p<0,01) were determined. Reproductive age increased this feature. In the feature specific gravity, T1 was 81.11, T0: 70.72. Highly significant differences (p<0,01) were calculated. Reproductive age increased this feature. In the parameter percentage of porous eggs, T1 was 2.2%, T0: 2.6%. No significant differences (p>0,05) were calculated. In the parameter of percentage of broken eggs, T1 was 0.8%, T0: 1.3%. Significant differences (p<0,05) were calculated. For the characteristic feed intake, T1 was 168.5g, T0: 170.88g. Highly significant differences (p<0,01) were determined. For the parameter feed conversion, T1 was 5.44, T0: 5.56. No significant differences (p>0,05) were determined. We conclude that the addition of a kilo of broiler breeders Biocalcio to week 59 to 66, improved growth performance and egg quality.